Suppression of High-Fat Diet–Induced Obesity by Platycodon Grandiflorus in Mice Is Linked to Changes in the Gut Microbiota. Issue 9 (8th June 2020) - Ke, Weixin; Bonilla-Rosso, Germán; Engel, Philipp; Wang, Pan; Chen, Fang; Hu, Xiaosong
ABSTRACT: Background: The root of Platycodon grandiflorus (PG) has a long-standing tradition in the Asian diet and herbal medicine, because of its anti-inflammatory and antiobesity effects. Changes in the gut microbiota can have dietary effects on host health, which suggests a relation between the 2. Objectives: The aim of our study was to investigate the relation between PG-mediated suppression of obesity and the composition and functioning of the gut microbiota. Methods: Six-week-old male C57BL/6J mice were fed either a control diet (CON, 10% kcal from fat), a high-fat diet (HFD, 60% kcal from fat), or a PG-supplemented HFD for 18 wk. PG was administered by oral gavage at 2 g · kg body weight −1 · d −1 . Body weight and food intake were monitored. Lipid metabolism, inflammation, and intestinal barrier function were determined. Amplicon sequencing of the bacterial 16S ribosomal RNA gene was used to explore gut microbiota structure, and nontargeted metabolomics analysis was performed to investigate metabolite concentrations in fecal samples. Results: We found that PG significantly ameliorated HFD-induced inflammation, recovered intestinal barrier integrity (reduced permeability by 39%, P  = 0.008), reduced fat accumulation by 26% ( P  = 0.009), and changed the expression of key genes involved in the development of white adipose tissue ( P  < 0.05) in HFD-fed mice to similar levels in CON mice. Moreover, PG attenuated HFD-induced changes in the gut microbiota; it especially increased Allobaculum (7.3-fold, P  = 0.002) relative to HFD, whereas CON was 15.2-fold of HFD ( P  = 0.002). These changes by PG were associated with an increase in the production of SCFAs (butyrate and propionate, P  < 0.001) and other carbohydrate-related metabolites known to have a major role in disease suppression. Conclusions: Our study demonstrated that PG beneficially changed the gut microbiota and the gut metabolome in HFD-fed mice, and suggests that the antiobesity effects of PG may be mediated via changes in gut microbiota composition and metabolic activity.